2018
DOI: 10.1007/s11882-018-0820-8
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture Occupational Exposures and Factors Affecting Health Effects

Abstract: Agriculture environments contain a variety of inflammatory aerosols that may increase risk for lung inflammation and disease in exposed individuals. In addition, epidemiological studies have also identified protective effects of rural environments and farming exposures. In this review, we will discuss recent literature published since 2016 that investigates the impact of differing agricultural exposures on respiratory health. Discussions include the impact of farming modernization, education and personal prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…The frequency of these personal protective practices was observed as low worldwide. 36 A previous study reported that reasons for not using protective equipment in farmers could be due to discomfort and inconvenience when working, 37 which is similar to our qualitative results. Washing hands was the most common practice among farmers.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of these personal protective practices was observed as low worldwide. 36 A previous study reported that reasons for not using protective equipment in farmers could be due to discomfort and inconvenience when working, 37 which is similar to our qualitative results. Washing hands was the most common practice among farmers.…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary disease is the leading cause of morbidity and mortality worldwide, with new threats emerging from vaping, rising air pollution, exposure from industrial farming, and worldwide pandemics, such as the infamous lung damaging coronavirus disease 2019 (Rattue, 2012;Guarascio et al, 2013;Nordgren and Bailey, 2016;Nordgren and Charavaryamath, 2018;Eskandari et al, 2019). COVID-19 has risen to be one of the biggest killers of 2020, which resulted in 5,817,385 confirmed cases and 362,705 deaths through May 30, 2020 (Stokes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat harvesting is also believed to be involved in other parts of the world where fungal spores are considered the predominant aeroaller [18]. Other antigens potentially involved are biological dust, such as dusts of plant, animal and microbial origin; the innate inflammatory response to biological dust involves several overlapping signaling pathways, including various kinomis (a set of protein kinases) that signal pathways in the lines of the epithelium and monocyte of the human airways and in the monocytic cell lines [19]. In addition, some spices induce the inflammatory reaction based on T-cells after the recognition of the contact of the antigen.…”
Section: Reviewsmentioning
confidence: 99%